Leukocyte adhesion-deficient neutrophils fail to amplify phagocytic function in response to stimulation. Evidence for CD11b/CD18-dependent and -independent mechanisms of phagocytosis. - Gresham, H D (1991)
Stimulation of PMN with inflammatory mediators markedly augments Fc and CR1 receptor-mediated ingestion. However, CD11/CD18-deficient PMN from three patients with complete leukocyte adhesion deficiency (LAD) failed to recruit phagocytic function in response to phorbol esters, cytokine, or Arg-Gly-Asp-containing ligand stimulation. Because stimulated ingestion is protein kinase C (PKC)-dependent, our data indicate that LAD PMN exhibit only PKC-independent phagocytosis. The defect in PKC-dependent ingestion is specific for CD11b/CD18 and not secondary to the chronic or recurrent infections which occur in this disease. The LAD phenotype for phagocytic function can be reproduced in normal PMN by the anti-CD11b MAbs OKM1 and OKM10. In contrast, MAb Mo1 (anti-CD11b) and MAb IB4 (anti-CD18) inhibit both CD11b/CD18-dependent and -independent mechanisms of ingestion by normal PMN. Their ability to inhibit CD11b/CD18-independent ingestion may be mediated by cAMP, as shown by experiments with a protein kinase A inhibitor HA1004 and by direct measurement of cAMP levels in immune complex- and FMLP-stimulated PMN. These data indicate that CD11b/CD18-independent and -dependent mechanisms of phagocytosis exist and that some effects of anti-CD11b/CD18 MAbs may be mediated by alterations in cAMP levels.